A closer look at chemotherapy‐induced flagellate dermatitis - A. Constantinou; D. Kotecha; P. Laouris; B. dePaula (Wiley, 2022)
Abstract Background Flagellate dermatitis (FD) is a rare skin rash, which may occur following the administration of antineoplastic agents. It has been reported following the administration of bleomycin, docetaxel, trastuzumab, cisplatin, bendamustine and doxorubicin. We provide a summary of the epidemiology, aetiology, pathophysiology, and distribution of chemotherapy‐induced FD. Methods PubMed was searched using ((flagellat*) AND (Dermat*)) OR ((Flagellat*) AND (Erythema)). The search yielded 206 publications, out of which 54 individual case reports were identified which fulfilled our inclusion criteria. Statistical analysis was performed where appropriate. Results Female patients were slightly more likely to develop FD compared to males. In the majority of cases FD appeared on the upper and lower limbs and pruritus was an accompanying feature in 51% of cases. Most cases developed after the first cycle of chemotherapy and females were statistically more likely to present within the first 72 hr (p <0.05). Skin biopsies were taken in 41% of cases and this was not statistically associated with the patient's gender, (p = 0.651), presentation within 72 hr (p = 0.076) or cancer diagnosis. Chemotherapy was stopped in 62% of patients and was associated with female gender (p = 0.0098). Most patients who received treatment were managed with topical steroids. Time for rash resolution ranged from a few weeks to four months following the discontinuation of the causative drug. Conclusion FD is a rare adverse skin effect of chemotherapeutic treatment, most commonly presenting on the upper and lower limbs of patients following their first cycle of chemotherapy. Early presentation is more common in females leading to increased likelihood of stopping chemotherapy. Biopsy findings poorly correlate with disease severity. Continuation of chemotherapy treatment in combination with topical steroids may not adversely affect rash resolution.